2019
DOI: 10.1111/sms.13583
|View full text |Cite
|
Sign up to set email alerts
|

Activity limitation and match load in para‐footballers with cerebral palsy: An approach for evidence‐based classification

Abstract: Classification is a hot topic in Paralympic sport, making the development of evidence‐based and sport‐specific classification systems mandatory. However, the development of measurements for exploring the relationships between the athletes' impairment and their activity limitation is a considerable scientific challenge in team Paralympic sport such as 7‐side football (ie, CP Football). The aims of this study were 1) to describe the activity limitation and external match load (ML) differences among impairment pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 32 publications
3
60
2
5
Order By: Relevance
“…It should be mentioned that the sport class distributions obey the para-sport rules, where two players of the sport classes FT5/FT6 must be on the field of play and no more than one FT8 player would be included in the line-up. Nevertheless, the large effect sizes when comparing FT8 para-footballers with the other three sport classes demonstrated that those with a lower level of impairment exhibit better sports performance [2][3][4]8,19,21,34]. In addition, it was found that FT6 players performed the worst in all the tests, reinforcing the idea that those with dyskinesia or ataxia would be those para-athletes in which brain injury may affect, to a higher extent, sports performance (i.e., limitation of activity) when multiple skills are required.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It should be mentioned that the sport class distributions obey the para-sport rules, where two players of the sport classes FT5/FT6 must be on the field of play and no more than one FT8 player would be included in the line-up. Nevertheless, the large effect sizes when comparing FT8 para-footballers with the other three sport classes demonstrated that those with a lower level of impairment exhibit better sports performance [2][3][4]8,19,21,34]. In addition, it was found that FT6 players performed the worst in all the tests, reinforcing the idea that those with dyskinesia or ataxia would be those para-athletes in which brain injury may affect, to a higher extent, sports performance (i.e., limitation of activity) when multiple skills are required.…”
Section: Discussionmentioning
confidence: 98%
“…Although test #1 does not really demand a COD due to it consisting of a straight-line sprint with ball dribbling, this study reports its reliability when ball dribbling is required in a shorter run as compared with the study by Reina et al [3], where para-athletes had to run 40 m with partial measurements at 10 m and 25 m. Our study exhibits better ICC values (0.95 vs 0.84 at 10 m, 0.76 at 25 m and 0.73 at 40 m) and similar SEM values (6.3% vs 4.5% at 10 m, 6.2% at 25 m, and 6.5% at 40 m). The 20 m sprint has been recently used to explore the relationships between performance and match load using GPS technology [21], but without involving ball skills during the test. Therefore, this study provides new evidence about the feasibility and reliability for implementing a sport-specific test that better replicates the demands of the real game [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations